DIPLOMASI INDONESIA DALAM UPAYA MENGAMBIL ALIH PENGENDALIAN WILAYAH UDARA DI KEPULAUAN RIAU DARI SINGAPURA TAHUN 2020-2022 - Kenny Eza Natawijaya; Muhammad Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research tries to explain how the development of diplomacy conducted by Indonesia in taking over control of the Flight Information Region (FIR) in the Riau Islands region from Singapore in 2020-2022. The management of the Flight Information Region (FIR) in the Riau Islands region from Singapore has a detrimental impact on Indonesia in the economic sector to Indonesia's security and defense. This research uses the realism perspective, diplomacy theory, state-level analysis, and qualitative research methods. This qualitative research method provides an analytical explanation related to the phenomenon of the research subject by trying to explain or explain how the Indonesian government's diplomacy is in taking back control of airspace in the Riau Islands from Singapore. The data collection technique used in this study is a library technique sourced from several books, journals, articles, news, and websites. The result of this study is that Indonesia and Singapore signed an agreement regarding the Realignment of FIR on January 25, 2022, in Bintan, Riau Islands. The agreement is a good achievement for Indonesia, such as the expansion of Jakarta's FIR coverage to the Riau Islands airspace. It shows that the diplomatic conducted by the Indonesian government for a long time have had good developments and successes for Indonesia. Keywords: Diplomacy, Flight Information Region (FIR), Kepulauan Riau, Take over.